Model Sociopreneur Desa dalam Pemberdayaan Pemuda Milenial sebagai Solusi Pengentasan Pengangguran dan Penguatan Ekonomi Kreatif di Desa Tarumajaya, Kecamatan Kertasari, Kabupaten Bandung - Soni Mulyawan Setiana; Dewi Kurniasih; Hetty Hassanah; Safina Rama Dewi; Zahra Mughni Yuniar; Alfi Nur Halim (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
Unemployment among millennial youth in rural areas remains a significant challenge that hinders the optimization of local resources. This Community Service Program aimed to empower the youth of Tarumajaya Village through the implementation of the Village Sociopreneur model as a solution to reduce unemployment while strengthening the creative economy sector. The program consisted of several stages, including socialization, training, barista practice, digital marketing, business legality awareness, mentoring, evaluation, and program sustainability. The results indicate that participants gained not only theoretical knowledge but also practical skills in coffee processing, digital marketing strategies, and business legality to ensure long-term sustainability. Evaluation using questionnaires revealed a very high level of satisfaction, with the majority of participants considering the materials highly relevant to their needs. In conclusion, the Village Sociopreneur model has proven effective in enhancing youth capacity, creating new business opportunities, and opening pathways for job creation that contribute to the growth of the rural creative economy.